Neuroprotective Effects of Cornus officinalis on Stress-Induced Hippocampal Deficits in Rats and H2O2-Induced Neurotoxicity in SH-SY5Y Neuroblastoma Cells - Weishun Tian; Jing Zhao; Jeong-Ho Lee; Md Rashedunnabi Akanda; Jeong-Hwi Cho; Sang-Ki Kim; Yu-Jin Choi; Byung-Yong Park (MDPI AG, 2019)
Oxidative stress plays a vital role in neurodegenerative diseases. Cornus officinalis (CC) has a wide range of pharmacological activities (e.g., antioxidant, neuroprotective, and anti-inflammatory). The present study was undertaken to elucidate the neuroprotective mechanism of CC and fermented CC (FCC) on stress and H2O2-induced oxidative stress damage in rats and SH-SY5Y cells. A dose of 100 mg/kg CC or FCC was orally administered to rats 1 h prior to immobilization 2 h per day for 14 days. CC, especially FCC administration decreased immobility time in forced swim test (FST), effectively alleviated the oxidative stress, and remarkably decreased corticosterone, β-endorphin and increased serotonin levels, respectively. In cells, CC and FCC significantly inhibited reactive oxygen species (ROS) generation, lactate dehydrogenase (LDH) release and significantly increased the genes expression of antioxidant and neuronal markers, such as superoxide dismutase (SOD), catalase (CAT), and brain-derived neurotrophic factor (BDNF). Moreover, the pro-apoptotic factor Bax and anti-apoptotic factor Bcl-2 (Bax/Bcl-2) ratio was regulated by CC and FCC pretreatment. Both in rats and cells, CC and FCC downregulated mitogen-activated protein kinase (MAPK) phosphorylation. Taken together, these results demonstrated that CC and particularly FCC ameliorated oxidative stress and may be used on the neuroprotection.